Pengaruh Karakteristik Eksekutf Dan Komite Audit Terhadap Tax Avoidance Dengan Leverage Sebagai Variabel Intervening - Elva Latifah Salsabila; Dewi Kusuma Wardani; Anita Primastiwi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
The purpose of this study was to examine the effect of executive and audit committee character on tax avoidance with leverage as an intervening variable. The population in this study is the manufacturing industry listed on the Indonesia Stock Exchange (IDX) during 2015-2019. The sample selection in this study used purposive sampling. The number of samples in this study were 55 manufacturing industry samples. Data were analyzed using Partial Least Square (PLS) with the support of the SmartPLS 3.0 application. The results of this study indicate that executive character has a positive effect on leverage. The audit committee has a negative effect on leverage. Leverage, executive character, and the audit committee have a positive effect on tax avoidance. Leverage is able to mediate the positive influence of executive and audit committee characters on tax avoidance